Antioxidant properties of a human neuropeptide and its protective effect on free radical‐induced DNA damage. (10th April 2014) - Mohseni, Simin; Emtenani, Shirin; Emtenani, Shamsi; Asoodeh, Ahmad
<x xml:space="preserve">Abstract</x> Human catestatin CgA352–372 (SL21) is an endogenous neuropeptide with multiple biological functions. The present study aimed to evaluate the antioxidant, antibacterial, cytotoxic, and DNA damage protective effects of SL21 neuropeptide. SL21 neuropeptide generated from the C‐terminus of chromogranin A (CgA) was synthesized by solid‐phase method. Synthetic peptide was subjected to various in vitro antioxidant assays including the scavenging of 1, 1‐diphenyl‐2‐pycryl‐hydrazyl (DPPH), 2, 2‐azino‐bis(3‐ethylbenzothiazoline‐6‐sulfonic acid) (ABTS·+), and hydroxyl free radicals, metal ion chelation, inhibition of lipid peroxidation, and reducing power. Moreover, protective effect of SL21 on H2O2‐induced DNA damage was analyzed using pTZ57/RT plasmid. Methylthiazoltetrazolium assay was also performed to study the cytotoxic effect of SL21 neuropeptide on human peripheral blood mononuclear cells. Furthermore, antibacterial and hemolysis assays were conducted. The results demonstrated high activities of SL21 in scavenging free radicals (DPPH, ABTS·+, and hydroxyl), chelating of Cu2+/Fe2+ metal ions, reducing power, and inhibition of lipid peroxidation in a concentration‐dependent manner. SL21 neuropeptide revealed a protective effect on DNA damage caused by hydroxyl radicals. Interestingly, the peptide exhibited no significant cytotoxicity towards peripheral blood mononuclear cells. Furthermore, SL21 peptide displayed antimicrobial activity against Staphylococcus aureus and Pseudomonas aeruginosa without any hemolytic activity on human red blood cells. Conclusively, the present study established SL21 (catestatin) as a novel antioxidative peptide that could further be investigated for its potential use as a pharmaceutical agent. Copyright © 2014 European Peptide Society and John Wiley & Sons, Ltd.